Click Chemistry-Inspired Synthesis and Photophysical Studies of Calix[4]arene-Cored Galactosylated and Mannosylated Glycodendrimers - Sunil Kumar; Mangal S. Yadav; Tarkeshwar Maddeshiya; Surabhi Asthana; Manoj K. Jaiswal; Vinod K. Tiwari; Mrituanjay D. Pandey (Organic Materials, 2023)
Abstract A prompt and modular copper(I)-catalyzed azide–alkyne cycloaddition ʼclickʼ approach has been exploited for the synthesis of galactose- and mannose-coated calixarene-cored G1 generation glycodendrimers. The developed calixarene glycodendrimers were characterized by using spectral techniques (1H NMR, 13C NMR and IR). In photophysical evaluation, UV and fluorescence spectra of the developed compounds were recorded in CH3CN/H2O.